PENGARUH METODE PEMBELAJARAN DRILL TERHADAP HASIL BELAJAR SISWA KELAS IV SDN 1 RANTAU BAYUR KABUPATEN BANYUASIN - Kirana Salsabilla; Kabib Sholeh; Sylvia Lara Syaflin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The problem of this research is motivated by the problems that occur, namely the low student learning outcomes in science learning caused by a lack of teachers involving students in the learning process so that students are less active when learning takes place and the teacher only uses the usual lecture method in providing learning material and lacks innovative learning methods so that students are less active in participating in learning and affect student learning outcomes. This study aims to determine whether or not there is an effect of the Driil learning method on the learning outcomes of fourth grade students at SDN 1 Rantau Bayur, Banyuasin Regency. The research method used is the Quasi Experiment design method with research design. The experimental research used in this study used the Control Group Design. Data collection techniques began with interviews, tests, and documentation. Data analysis used normality test, homogeneity test, independent sample t-test (t-test). Based on the results of the study, it showed that this drill learning method had an effect on student learning outcomes in science learning on force and motion in class IV with the posttest average score in the experimental class (85.5) which was superior to the posttest results in the control class (56). and the results of the calculation of the t-test whose truth is obtained sig (2-tailed) = 0.000 <0.05 and thit = 9.042 > ttable = 1.686 thus 0.000 <0.05 and thit = 9.042 > ttable = 1.686 then Ho is rejected and Ha accepted. or there is a significant influence on the drill learning method on student learning outcomes in the science subject at SDN 1 Rantau Bayur, Banyuasin Regency Keywords: Learning Outcomes, Science, Drill Method